Infertility following trisomic pregnancies : A nationwide cohort study - Wedenoja, Satu; Pihlajamäki, Mika; Gissler, Mika; Wedenoja, Juho; Öhman, Hanna; Heinonen, Seppo; Kere, Juha; Kääriäinen, Helena; Tanner, Laura (John Wiley & Sons, 2025)
Objective: To study whether gynecologic or reproductive disorders show association with trisomic conceptions.
Methods: This nationwide cohort study utilized the Registry of Congenital Malformations to identify women who had a trisomic pregnancy (n = 5784), either with trisomy 13 (T13; n = 351), trisomy 18 (T18; n = 1065) or trisomy 21 (T21; n = 4369) from 1987 to 2018. We used the Finnish Maternity cohort to match the cases to population controls (n = 34 422) on the age, residence, and timing of pregnancy. These data were cross-linked to the ICD-10 diagnoses of the national Care Registry for Health Care data on specialized health care in Finland during 1996 to 2019. Both inflammatory (ICD-10 diagnoses: N70-N77) and noninflammatory disorders of the genital tract (N80-N98) were studied. Crude odds ratios (ORs) with 95% CIs were calculated for associations between diagnoses and trisomic conceptions.
Results: The diagnosis of female infertility (N97) at any time was associated with trisomic conceptions (OR: 1.19, 95% CI: 1.08-1.32). In the subgroup analysis, this association was found for T18 (OR: 1.29, 95% CI: 1.03-1.61) and T21 (OR: 1.17, 95% CI: 1.04-1.32), but not for T13 (OR: 1.15, 95% CI: 0.75-1.72). When restricting the timing of the diagnosis of female infertility, an elevated OR was found only after the index pregnancy (OR: 1.81, 95% CI: 1.56-2.09). These increased odds for infertility after trisomic conceptions were observed both in women <35 years (T18 OR: 1.91, 95% CI: 1.21-3.00; T21 OR: 1.68, 95% CI: 1.31-2.14) and in women ≥35 years (T18 OR: 2.17, 95% CI: 1.40-3.33; T21 OR: 1.87; 95% CI: 1.47-2.39), but not after T13 conceptions.
Conclusion: Our observational data suggest a link between trisomic conceptions and subsequent diagnoses of infertility but do not demonstrate causality. These data implicate that partially similar mechanisms might predispose to trisomy and infertility, regardless of maternal age.